2021
DOI: 10.3389/fnut.2021.756565
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Aryl Hydrocarbon Receptor and Gut Microbiota-Derived Metabolites Indole-3-Acetic Acid in Sulforaphane Alleviates Hepatic Steatosis in Mice

Abstract: Scope: Gut microbiome-derived metabolites are the major mediators of diet-induced host-microbial interactions. Aryl hydrocarbon receptor (AHR) plays a crucial role in glucose, lipid, and cholesterol metabolism in the liver. In this study, we aimed to investigate the role of indole-3-acetic acid (IAA) and AHR in sulforaphane (SFN) alleviates hepatic steatosis in mice fed on a high-fat diet (HFD).Methods and Results: The HFD-fed male C57BL/6 mice were intervened with SFN for 6 weeks. HFD-mice showed classical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…A previous study suggested that Lactobacillus casei intervention ameliorates the gut healthy by promoting the production of pipecolinic acid [45]. Gut microbiome-derived 3-indole propionic acid and indole-3-acetic acid act as the microbiota-speci c AhR ligand, and their concentrations are negatively associated with the relative abundance of Bi dobacterium [46][47]. Among these, indole-3-acetic acid alleviates LPSstimulated in ammatory response and free radical generation by regulating the expression of HO-1 and eliminating the free radicals [48].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that Lactobacillus casei intervention ameliorates the gut healthy by promoting the production of pipecolinic acid [45]. Gut microbiome-derived 3-indole propionic acid and indole-3-acetic acid act as the microbiota-speci c AhR ligand, and their concentrations are negatively associated with the relative abundance of Bi dobacterium [46][47]. Among these, indole-3-acetic acid alleviates LPSstimulated in ammatory response and free radical generation by regulating the expression of HO-1 and eliminating the free radicals [48].…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, 3-IAA was negatively associated with adherence to the MDS and AHEI. Both 3-IAA and 3-IPA have shown antioxidant and low pro-oxidative properties [ 43 , 44 ] and immune regulation through the activation of the aryl hydrocarbon receptor [ 45 , 46 ], and 3-IPA has been inversely associated with diabetes and inflammation [ 47 ]. The divergent association between IPA and IAA may have resulted from microbial changes, as dietary patterns have been shown to change gut microbiota composition [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 78 Reportedly, microbiota-derived indole and 5-HT improved hepatic steatosis and gut-barrier function. 79 …”
Section: Microbiota-derived Metabolitesmentioning
confidence: 99%
“…Indole and its derivatives, including indole-3-propionic acid (IPA), indole-3-aldehyde (I3A), indoleacrylic acid, and indole-3-acetic acid (IAA), are aryl hydrocarbon receptors (AhRs) agonists to stimulate CD4+ T cells differentiation toward regulatory T cells and regulate lipid metabolism. 79 In inflammatory bowel disease (IBD), indole alleviated intestinal inflammation by upregulating interleukin 22 (IL-22) and downregulating interferon gamma in lamina propria mononuclear cells. 78 Among NAFLD patients, the plasmatic indole concentration was inversely correlated to hepatic fat content and pro-inflammatory macrophage polarization.…”
Section: Microbiota-derived Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation